2009
DOI: 10.3324/haematol.2009.010546
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability in splenectomized thalassemic patients detected by whole-blood thromboelastometry, but not by thrombin generation in platelet-poor plasma

Abstract: BackgroundThe mechanisms responsible for the increased thrombotic risk associated with thalassemia are still unclear. They might be related to the effects of red blood cell or endothelial cell derangements, increased numbers of platelets as well as abnormal plasma coagulation. Design and MethodsTo evaluate the relative role played by cells and plasma we investigated 169 patients with thalassemia by means of thromboelastometry and thrombin generation tests. Thromboelastometry measures indices of the viscoelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…36 All the thromboelastometry parameters determined in whole blood, including shortened clotting time and clot formation time, and increased maximum clot firmness, were consistent with hypercoagulability, especially in splenectomized patients. However, thrombin generation determined in platelet-poor plasma was not significantly different from that in healthy individuals.…”
mentioning
confidence: 84%
“…36 All the thromboelastometry parameters determined in whole blood, including shortened clotting time and clot formation time, and increased maximum clot firmness, were consistent with hypercoagulability, especially in splenectomized patients. However, thrombin generation determined in platelet-poor plasma was not significantly different from that in healthy individuals.…”
mentioning
confidence: 84%
“…Other negative effects include a raised risk of thrombotic complications and pulmonary hypertension, possibly due to the raised number of circulating platelets and immature red blood cells with alteration of the endothelial function, enhanced platelet activation, decreased levels of proteins C and S [16,17] Then, a progressive increase of awareness of these negative effects may have contributed to lower the tendency to perform splenectomy in these b-TM patients. Many studies have suggested that the rate of alloimmunization is higher after splenectomy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Such risk-assessment models should be established for patients with thalassemia and could be used to identify high-risk patients and to target them for further testing and close follow-up. Several diagnostic tests are under investigation and could help further identify patients at highest risk, approaching an evidence-based medicine model [58]. Finally, evidence from observational studies should be carried forward to clinical trials, evaluating the role of transfusion, antiplatelet and anticoagulant therapy for the prevention of thrombotic events in thalassemia patients.…”
Section: Five-year Viewmentioning
confidence: 99%